The Accumulating Costs Hypothesis—to Better Understand Delayed “Hidden” Costs of Seemingly Mild Disease and Other Moderate Stressors - Hasselquist, Dennis; Tobler, Michael (Frontiers in Ecology and Evolution, 2021)
Mild diseases and moderate stressors are seemingly harmless and are therefore often assumed to have negligible impact on Darwinian fitness. Here we argue that the effects of ‘benign’ parasites and other moderate stressors may have a greater impact on lifespan and other fitness traits than generally thought. We outline the ‘accumulating costs’ hypothesis which proposes that moderate strains on the body caused by mild diseases and other moderate stressors that occur throughout life will result in small irreversible ‘somatic lesions’ that initially are invisible (i.e., induce ‘hidden’ costs). However, over time these somatic lesions accumulate until their summed effect reaches a critical point when cell senescence and malfunction begin to affect organ functionality and lead to the onset of degenerative diseases and aging. We briefly discuss three potential mechanisms through which the effects of moderate strains (e.g., mild diseases) could accumulate: accelerated telomere shortening, loss of repetitious cell compartments and other uncorrected DNA damage in the genome. We suggest that telomere shortening may be a key candidate for further research with respect to the accumulating costs hypothesis. Telomeres can acquire lesions from moderate strains without immediate negative effects, lesions can be accumulated over time and lead to a critically short telomere length, which may eventually cause severe somatic malfunctioning, including aging. If effects of mild diseases, benign parasites and moderate stressors accrued throughout life can have severe delayed consequences, this might contribute to our understanding of life history strategies and trade-offs, and have important implications for medicine, including consideration of treatment therapies for mild (chronic) infections such as malaria.